DNA methylation analysis of cord blood samples in neonates born to gestational diabetes mothers diagnosed before 24 gestational weeks. Issue 1 (19th January 2022) - Kasuga, Yoshifumi; Kawai, Tomoko; Miyakoshi, Kei; Hori, Asuka; Tamagawa, Masumi; Hasegawa, Keita; Ikenoue, Satoru; Ochiai, Daigo; Saisho, Yoshifumi; Hida, Mariko; Tanaka, Mamoru; Hata, Kenichiro
Abstract : Introduction: Genome-wide methylation analyses of gestational diabetes mellitus (GDM) diagnosed after 24 gestational weeks (late GDM (L-GDM)) using cord blood have been reported. However, epigenetic changes in neonates born to mothers with GDM diagnosed before 24 gestational weeks (early GDM (E-GDM)) have not been reported. We investigated DNA methylation in neonates born to mothers with E-GDM using cord blood samples. Research design and methods: Genome-wide DNA methylation analysis was performed using an Illumina EPIC array to compare methylation rates of 754 255 autosomal sites in cord blood samples from term neonates born to 162 mothers with GDM (E-GDM: n=84, L-GDM: n=78) and 60 normal glucose tolerance (normal OGTT) pregnancies. GDM was diagnosed based on Japan Society of Obstetrics and Gynecology criteria modified with International Association of Diabetes in Pregnancy Study Group criteria. In this study, all GDM mothers underwent dietary management, while self-monitoring of blood glucose and insulin administration was initiated when dietary modification did not achieve glycemic control. Results: There were no significant differences in genome-wide DNA methylation of cord blood samples between the GDM (E-GDM and L-GDM) groups and normal OGTT group or between the E-GDM and normal OGTT groups, L-GDM and normal OGTT groups, and E-GDM and L-GDM groups. Conclusions: This is the first report to determine the DNA methylation patterns in neonates born to mothers with E-GDM. Neonates born to mothers with GDM, who were diagnosed based on Japan Society of Obstetrics and Gynecology criteria, may not differ in DNA methylation compared with those born to normal OGTT mothers.